2021
DOI: 10.1140/epjc/s10052-021-09193-7
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes and their anomalous behavior for black holes in f(R) gravity

Abstract: We study the propagation of scalar fields in the background of an asymptotically de Sitter black hole solution in f(R) gravity. The aim of this work is to analyze in modified theories of gravity the existence of an anomalous decay rate of the quasinormal modes (QNMs) of a massive scalar field which was recently reported in Schwarzschild black hole backgrounds, in which the longest-lived modes are the ones with higher angular number, for a scalar field mass smaller than a critical value, while that beyond this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 88 publications
0
11
0
1
Order By: Relevance
“…However, when M 2 Λ increases, the black hole becomes extremal when 9M 2 Λ = 1, and the critical mass value does not depend on the overtone number. The same behaviour was observed in the context of f (R) gravity [21]. The solution for the function F (y) is assumed to be a finite linear combination of the Chebyshev polynomials and can be plugged into the differential equation for F (y).…”
Section: Reissner-nordstr öM Anti De Sitter Quasinormal Modesmentioning
confidence: 59%
See 2 more Smart Citations
“…However, when M 2 Λ increases, the black hole becomes extremal when 9M 2 Λ = 1, and the critical mass value does not depend on the overtone number. The same behaviour was observed in the context of f (R) gravity [21]. The solution for the function F (y) is assumed to be a finite linear combination of the Chebyshev polynomials and can be plugged into the differential equation for F (y).…”
Section: Reissner-nordstr öM Anti De Sitter Quasinormal Modesmentioning
confidence: 59%
“…The study of the anomalous decay of QNMs was extended to f (R) modified gravity in [16][17][18][19][20]. In [21] asymptotically de Sitter black holes solutions of f (R) modified gravity were considered as background. The motivation of [21] was to investigate the competing effects of the cosmological term and the non-linear curvature terms on the behaviour of QNMs and QNFs generated by massless or massive scalar field perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature has lead the search and analysis of QNM to be an important subject in the gravitationalwave literature. Hence, one can use gravitational-wave observations in order to test general relativity, examining for instance the validity of the "no-hair theorem" [74][75][76], and use the predictions of QNM properties to constrain and classify modified gravity theories [77][78][79][80][81][82][83][84][85]. Furthermore, the QNM frequency can also partly reveal the stability of spacetime geometry under small perturbations [86,87].…”
Section: Introductionmentioning
confidence: 99%
“…The parameter β, which makes this solution different from the Schwarzschild-(anti-)de Sitter one, leads to a modified Newtonian dynamics (MOND) [28] which has been investigated in regard of deviations in the trajectories of massive bodies in the solar system which would follow from an entropic force [29], of possible phase transitions [30], and as a solution of the galaxy rotation curves problem [21]. Studies of the quasi-normal frequencies of vibrations of this black hole [31,32], and of their anomalous behavior [33], have showed that the strong cosmic censorship conjecture can be violated for some choices of the black hole parameters [34].…”
Section: Introductionmentioning
confidence: 99%